Higher Education and the SDGs in Africa: More of the Same? - Teferra, Damtew (International Higher Education, 2020)
There has been much talk about the increased focus on higher education in the Sustainable Development Goals. Yet, when compared with the preceding Millennium Development Goals, the new framework actually includes very few references to higher education. Africa would do better to focus its development efforts around other, more relevant, local and regional policies, which recognize the crucial role of higher education in development.